Paradigm of Integration of Islamic and Scientific Knowledge: Philosophical Reflection on Islamic Basic Education - Saleh, Mhd; Sutrisno, Sutrisno; Arifin, Zainal; Maemonah, Maemonah; Solihin, Rahmat (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to find the concept and paradigm of the integration of Islamic science and science in Islamic elementary education by examining the idea of the integration of Islamic science and science in higher education and then reflecting it into the context of Islamic elementary education. This study uses a qualitative approach with a type of literature. Data were collected from the literature on integrating Islamic science and science in higher education. The data that has been collected has then been analyzed using the content analysis method. The results of the analysis in the form of the concept and paradigm of the integration of Islamic science and science in higher education were then discussed with curriculum integration experts, elementary education experts, and Islamic religious education experts to reflect it into the context of Islamic elementary education. This study explains that the concept used in integrating Islamic science and science in Islamic elementary education combines the following ideas: Islamisasi Ilmu, Pengilmuan Islam, Integrasi-Interkoneksi in higher education. The paradigm and concept of developing the integration of Islamic science and science in Islamic elementary education is carried out in six steps, namely, development of the integration paradigm, preparation of the curriculum, identification of related Islamic science and science, designing learning, reflection, and innovation.